Investigating body constitution and infertility: a Traditional Chinese Medicine perspective - Lim, Chloe Chin Ching (Nanyang Technological University, 2024)
Infertility is the inability to get pregnant after one year of regular and unprotected sexual intercourse, affecting 15% of couples in Singapore. In Singapore, the childbearing age has increased from 30.6 in 2018 to 31.9 in 2022. As a consequence of delaying parenthood, there has been an increase in the number of women experiencing difficulty getting pregnant and higher risks for pregnancy and childbirth complications. This study aims to investigate the Traditional Chinese Medicine (TCM) Nine Body Constitutions (BC) amongst the women of childbearing age and understand how various lifestyle factors correlate to the respective TCM BC. It is hoped that identifying the various BC and lifestyle factors affecting their TCM BC, coupled with TCM treatment, individualized and targeted pre-pregnancy body conditioning treatment can be provided so that the body can be in the optimal state of yin and yang equilibrium, increase the pregnancy rate, shorten the conception time, reduce the rate of spontaneous or threatened abortion and reduce the risk of adverse pregnancy.